Refrigerated storage of fresh-cut marolo (Annona crassiflora mart.) - Della Lucia, Flávia; Ferreira, Eric Batista; Veiga, Sandra Maria Oliveira Morais; Azevedo, Luciana; Moreira, Marcela Aparecida Miranda; Vilas Boas, Eduardo Valério de Barros (Revista Brasileira de Agrotecnologia, 2020)
Marolo is a fruit typical of the Brazilian Savanna that is highly appreciated for its exotic flavour, nutritional value and sensory attributes. This study aimed to assess the quality of fresh-cut marolo by checking for possible changes in physical, chemical, microbiological and sensorial characteristics during cold storage (12 days at 0°C, 5°C and 10°C). Firmness varied based on storage time; the fruit softened on the 8th day and then increased in hardness until the end of the study. The lowest storage temperatures reduced the darkening rate of this product. No variations in the levels of soluble solids (12.7 to 14.6°B) or total phenolics (741.06 to 1295.21 mg. GAE.100g-1) were observed. Fruits stored at 10 °C showed an increase in titratable acidity after the 5th day and an increase in pH on the 10th and 12th days. Increases in the soluble pectin (156 to 265.73 mg.100g-1) and total pectins (>1.000 mg.100g-1) were noted. No significant difference was observed in the count of the total and thermotolerant coliforms, and the growth of filamentous fungi and yeasts decreased after storage at 0°C and 5°C after the 5th day. Storage at 5 °C for 5 days was found to be the most efficient set of conditions for maintaining the physical, chemical, microbiological and sensory characteristics of marolo.